Electroencephalography profiles as a biomarker of wellbeing: A twin study. (July 2020) - Chilver, Miranda R.; Keller, Arielle S.; Park, Haeme R.P.; Jamshidi, Javad; Montalto, Arthur; Schofield, Peter R.; Clark, C. Richard; Harmon-Jones, Eddie; Williams, Leanne M.; Gatt, Justine M.
Abstract: Alterations to electroencephalography (EEG) power have been reported for psychiatric conditions such as depression and anxiety, but not for mental wellbeing in a healthy population. This study examined the resting EEG profiles associated with mental wellbeing, and how genetics and environment contribute to these associations using twin modelling. Mental wellbeing was assessed using the COMPAS-W Wellbeing Scale which measures both subjective and psychological wellbeing. In 422 healthy adult monozygotic and dizygotic twins aged 18–61 years, we examined the association between mental wellbeing and EEG power (alpha, beta, theta, delta) using linear mixed models. This was followed by univariate and multivariate twin modelling to assess the heritability of wellbeing and EEG power, and whether the association was driven by shared genetics or environment. A significant association between wellbeing and an interaction of alpha, beta, and delta (ABD) power was found (β = −0.33, p < 0.001) whereby a profile of high alpha and delta and low beta was associated with higher wellbeing, independent of depression and anxiety symptoms. This finding was supported by a five-fold cross-validation analysis. A significant genetic correlation ( r G = −0.43) was found to account for 94% of the association between wellbeing and the EEG power interaction. Together, this study has identified a novel EEG profile with a common genetic component that may be a potential biomarker of mental wellbeing. Future studies need to clarify the causal direction of this association. Highlights: Resting electroencephalography EEG power is a robust measure of brain activity. Higher wellbeing is associated with high alpha and delta power and low beta power. The association between wellbeing and EEG power is due to shared genetics. Wellbeing is moderately heritable. EEG power shows moderate to strong heritability.